(untitled) (Journal of human and social sciences, 2019)
This study aims to explore the Libyan political and administrative context from the perspective of activating the role of local governance with the support of civil society institutions, within the framework of key concepts such as decentralization, local governance, and civil society organizations. The study seeks to shed light on the scope and outcomes of civil society participation in the political process in Libya as a support for local governance. Furthermore, it examines the roles, programs, and campaigns through which the concept of partnership between the central government, local governance, civil society, and various social forces and frameworks is promoted. Consequently, this approach contributes to strengthening shared responsibility, enhancing community initiatives to build the capacities of local councils, improving coordination between local councils, emphasizing constitutional arrangements, reinforcing the regulatory and oversight functions, supporting the electoral process, and promoting transparency within the political system.